PREPARING TEENS AND YOUNG MEN/WOMEN OF HKBP RESORT BINTANG BAYU DISTRICT XIV TEBING TINGGI DELI TO BECOME CHRISTIAN LEADERS IN THE FUTURE - Sitanggang, Pintor Marihot; Coornova Purba, Catrine Anna; Sibuea, Andreas Filemon; Wijanarko, Alwin; Hutahaean, Benny Octavianus (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
As the next generation of the nation and also the future of Christianity, teenagers and Christian youth must be prepared properly. In addition to blessing the teenagers and youth of the church with science and education that is qualified and ready to compete scientifically, teenagers and youth must also receive or be equipped spiritually, namely fostering their spirituality and morality so that they can grow and develop as a whole easy generation. Where capable in science (education) as well as having strong and resilient faith or spirituality. In the implementation of community service at HKBP Silau Dunia Resort Bintang Bayu District XIV Tebing Tinggi Deli, a motivational seminar was held with the theme of preparing teenagers and youth of HKBP Resort Bintang Bayu to become Christian leaders in the future. This motivational seminar is a coaching step for teenagers and church youth so that they can prepare and organize themselves to become a leader in the future and will build their personality as a leader who has strong faith and spirituality.